Governance Innovations and Population Data Recording in Southeast Aceh Regency - Muhamad Husein Maruapey (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
Population data management involves many complex activities of different types of organizations, stakeholders, and knowledge. Innovation is essential in improving the efficiency of the public sector. Governance innovations will give the consequences of the success of innovation itself.  Good governance is a reflection of the innovation strategy of a government administration process. The focus of this research is to investigate the phenomenon of innovation in the management of population data and documents in Southeast Aceh regency. The qualitative method with phenomenological analysis is used to explain and identify how the phenomenon occurs.  The data collection is done inductively by having interviews, discussions, and participatory observation. The triangulation approach is used to explain empirical and secondary data. The results of this study found that the management of innovation should be supported by various supporting policies and the leadership capacity of policy maker. Community participation and cross-border cooperation also contributed to the management of innovation. Innovation is also an immediate need today to deliver excellent public services by the government. JEL Classification:  H70, O32, R58